KONSEP PERTUNANGAN DALAM PERSPEKTIF AGAMA : STUDI KOMPERATIF AGAMA ISLAM DAN KRISTEN - Arif Sugitanata; Abdulrozak (Indonesian Association of Islamic Family Law Lecturers, 2020)
The purpose of this paper is to know concept of engagement in Islam and Christianity, then find the similarities by using literature study, because the materials and data in its preparation use holy book, books, and related literacy, then the data used in this paper is a qualitative and the method used is descriptive. Begins with the understanding of the engagement of the two religions, the author concludes a similarity that can be drawn, namely the engagement is an attempt by the two brides the choose, know, and understand each other before stepping up the dream of marriage. Of the objectives also include the definition of engagement which is choosing, knowing and understanding each other to carry out and make heart choices to create a harmonious family. Regarding the cancellation of the engagement there are similarities in which there is room to be canceled with various established reasons